Development of an Intelligent System for Early Diagnosis of Diseases in Toddlers Using Forward Chaining and Dempster-shafer Integration - Pratama, Yusuf Hendra; Firmansyah, Firmansyah; Arfin, Ahmad (APIC, 2025)
Toddlerhood is an important period in a child's growth and development. In this period children will be vulnerable to disease. There are several types of diseases that range in toddlers such as diarrhea, pneumonia, malaria, etc. The problems faced are the limited access and quality of health services in some areas where health costs are still relatively high, the availability of health workers is also not always available, and the lack of knowledge related to toddler health. So, a system is needed that can provide knowledge and first aid information related to the health of toddlers which is expected to help in reducing the mortality rate of toddlers, especially for the types of diseases that can cause death such as diarrhea, pneumonia and malaria. The methods used in this research are Forward Chaining and Dempster-shafer. The result of this research is an intelligent system that applies forward chaining and dempster-shafer methods to diagnose early diseases in toddlers. The test results carried out in this research show an accuracy value of 90% of 10 tests. The results of Blackbox and usability testing conducted also show that the developed system is as expected and feasible to use